2020
DOI: 10.3389/fmed.2020.00142
|View full text |Cite
|
Sign up to set email alerts
|

Austrian Syndrome in an Immunocompromised Patient—A Case Report

Abstract: Austrian syndrome consists of a triad of endocarditis, meningitis, and pneumonia caused by Streptococcus pneumoniae. With the arrival of many antibiotic therapies, the disease remains rare, however, it can be overlooked due to the lack of awareness. We present a case of Austrian syndrome in an immunocompromised patient complicated by multiorgan failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For the purpose of the review, we adopted the common definition of Austrian syndrome - the triad of endocarditis, meningitis and pneumonia caused by Streptococcus pneumoniae . 10 , 11 , 12 , 13 , 14 Isolation of Streptococcus pneumoniae could be by culture, PCR or antigen testing. We arrived at a consensus for defining each component of the triad to meet our inclusion criteria ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of the review, we adopted the common definition of Austrian syndrome - the triad of endocarditis, meningitis and pneumonia caused by Streptococcus pneumoniae . 10 , 11 , 12 , 13 , 14 Isolation of Streptococcus pneumoniae could be by culture, PCR or antigen testing. We arrived at a consensus for defining each component of the triad to meet our inclusion criteria ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The authors emphasized the good outcome despite risk factors and multiorgan failure 2 . Jesus et al previously reported a healthy 67-year-old woman with sudden coma, hypoxemia, tachycardia, hypotension, acute renal failure, meningitis, and the presence of pneumococcus in cultures of blood, cerebrospinal fluid and the bronchial secretions 4 .…”
mentioning
confidence: 99%
“…
Streptococcus pneumoniae (pneumococcus) was first isolated in 1880 by George Miller Sternberg in the United States and by Louis Pasteur in France, followed by its association with arthritis, otitis media, lobar pneumonia, meningitis, and endocarditis 1 . Classical Austrian syndrome (AS) includes the triad of endocarditis, meningitis, and pneumonia by pneumococcus, a condition with approximately 80 case descriptions [2][3][4][5][6][7] . The main risk factors are alcoholism, immunosuppression, smoking, aging, and drug abuse.
…”
mentioning
confidence: 99%